Gambaran Kualitas Hidup pada Pasien Gagal Ginjal Kronis yang Menjalani Hemodialisa di RSUD Ibu Fatmawati Soekarno Surakarta - Rasianti Puspita Sari; Sitti Rahma Soleman (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Chronic Kidney Failure is a condition when kidney function is impaired because it cannot filter blood normally. Patients with kidney failure will experience impaired function of regulating fluid and electrolyte balance. This condition can occur over the years which is progressive and irreversible, requiring hemodialysis therapy. Kidney damage can reduce a person's quality of life. Quality of life includes physical dimensions, psychological dimensions, social dimensions, and environmental dimensions. Objective: Knowing the description of quality of life in chronic renal failure patients undergoing hemodialysis at RSUD Ibu Fatmawati Soekarno Surakarta. Method: This type of research uses descriptive methods with a quantitative approach. The patient sample size was 44 respondents with Accidental Sampling. Measurement of quality of life using the Kidney Disease Quality of Life Short Form 1.3 (KDQOL SFTM 1.3) questionnaire. Result: The results of this study indicate that chronic renal failure patients undergoing hemodialysis have a good quality of life as many as 15 respondents (34,1%) and very good 23 respondents (52,3%) while 6 respondents (13,6%) have a moderate quality of life. Conclusion: Chronic renal failure patients have a good quality of life at RSUD Ibu Fatmawati Soekarno Surakarta.